The Structure and Function of Acylglycerophosphate Acyltransferase 4/ Lysophosphatidic Acid Acyltransferase Delta (AGPAT4/LPAATδ) - Zhukovsky, Mikhail A.; Filograna, Angela; Luini, Alberto; Corda, Daniela; Valente, Carmen (Frontiers in Cell and Developmental Biology, 2019)
Lipid-modifying enzymes serve crucial roles in cellular processes such as signal transduction (producing lipid-derived second messengers), intracellular membrane transport (facilitating membrane remodeling needed for membrane fusion/fission), and protein clustering (organizing lipid domains as anchoring platforms). The lipid products crucial in these processes can derive from different metabolic pathways, thus it is essential to know the localization, substrate specificity, deriving products (and their function) of all lipid-modifying enzymes. Here we discuss an emerging family of these enzymes, the lysophosphatidic acid acyltransferases (LPAATs), also known as acylglycerophosphate acyltransferases (AGPATs), that produce phosphatidic acid (PA) having as substrates lysophosphatidic acid (LPA) and acyl-CoA. Eleven LPAAT/AGPAT enzymes have been identified in mice and humans based on sequence homologies, and their localization, specific substrates and functions explored. We focus on one member of the family, LPAATδ, a protein expressed mainly in brain and in muscle (though to a lesser extent in other tissues); while at the cellular level it is localized at the trans-Golgi network membranes and at the mitochondrial outer membranes. LPAATis a physiologically-essential enzyme since mice knocked-out for Lpaatδ show severe dysfunctions including cognitive impairment, impaired force contractility and altered white adipose tissue. The LPAATphysiological roles are related to the formation of its product PA. PA is a multifunctional lipid involved in cell signalling as well as in membrane remodelling. In particular, the LPAAT-catalyzed conversion of LPA (inverted-cone-shaped lipid) to PA (cone-shaped lipid) is considered a mechanism of deformation of the bilayer that favors membrane fission. Indeed, LPAAT is an essential component of the fission-inducing machinery driven by the protein BARS. In this process, a protein-tripartite complex (BARS/14-3-3phosphoinositide kinase PI4KIIIis recruited at the trans-Golgi network, at the sites where membrane fission is to occur; there, LPAATdirectly interacts with BARS and is activated by BARS. The resulting formation of PA is essential for membrane fission occurring at those spots. Also in mitochondria PA formation has been related to fusion/fission events. Since PA is formed by various enzymatic pathways in different cell compartments, the BARS-LPAAT interaction indicates the relevance of lipid-modifying enzymes acting exactly where their products are needed (i.e., PA at the Golgi membranes).